In the eye of the storm: Firms, putty-clay and capital destruction - Martino Pelli; Jeanne Tschopp; Natalia Bezmaternykh; Kodjovi M. Eklou (University of Bern, Department of Economics, 2020)
In this paper we provide a new identification strategy to test for the presence of putty-clay capital, i.e. capital that once installed cannot be re-invested. Using a panel of Indian manufacturing firms between 1995 and 2006, we quantify the response of firm sales within and across industries to an exogenous negative shock to the firm capital stock and find effects akin to Schumpeterian creative destruction, where surviving firms build back better. We show that within an industry, the sales of less productive firms decrease disproportionately more, while across industries capital destruction leads to a shift in sales towards more performing industries; which is consistent with a putty-clay technology. As a source of shock, we use a novel measure of firm exposure to storms based on the maximum wind speed exerted by each storm on each of the postal codes where the headquarters and the establishments of a firm are located. We establish that, depending on their strength, storms destroy up to 75.3% of the fixed assets of the median firm (in terms of its productivity and industry performance) and cause a decrease in its sales that can reach 99%.
Keywords: D22; D24; D25; Q54; 330; firms; putty-clay capital; creative destruction; storms